Significantly Improved Pharmacokinetics Enhances In Vivo Efficacy of APX001 against Echinocandin- and Multidrug-Resistant Candida Isolates in a Mouse Model of Invasive Candidiasis - Zhao, Yanan (Antimicrob Agents Chemother, 2018)
APX001 is a first-in-class, intravenous and orally available, broad-spectrum antifungal agent in clinical development for the treatment of life-threatening invasive fungal infections. The half-life of APX001A, the active moiety of APX001, is significantly shorter in mice than in humans (1.4 to 2.75 h in mice versus 2 to 2.5 days in humans), making the exploration of efficacy in mouse models difficult. After pretreatment with 1-aminobenzotriazole (ABT), a nonspecific cytochrome P450 inhibitor, greatly increased plasma APX001A exposure was observed in mice of different strains and of both genders. As a consequence, 26 mg/kg APX001 plus ABT sterilized kidneys in mice infected with Candida albicans, while APX001 alone at the same dose resulted in a modest burden reduction of only 0.2 log(10) CFU/g, relative to the vehicle control. In the presence of ABT, 2 days of once-daily dosing with APX001 at 26 mg/kg also demonstrated significant in vivo efficacy in the treatment of Candida glabrata infections in mice. Potent kidney burden reduction was achieved in mice infected with susceptible, echinocandin-resistant, or multidrug-resistant strains. In contrast, the standard of care (micafungin) was ineffective in treating infections caused by the resistant C. glabrata isolates.